Bridging the Local Digital Readiness Gap: Evidence from IKD Implementation in Waiheru Village, Ambon City - Normawati Normawati; Humairah Almahdali; La Madjid (Universitas Medan Area, 2026)
The Digital Population Identity (Identitas Kependudukan Digital/IKD) program is part of Indonesia's digital government agenda, yet its local implementation depends on more than application availability. This study analyzes the effectiveness of IKD implementation in Waiheru Village, Ambon City, through four digital governance dimensions: accessibility, service efficiency, institutional readiness, and trust-based participation. Using a descriptive qualitative design, data were collected through 14 semi-structured interviews with the village head, civil administration staff, community leaders, IKD users, and non-users, supported by two focus group discussions, observation at the village office, and document review. Thematic analysis shows that IKD has begun to support faster identity verification, but its effectiveness remains limited by unequal digital access, low user capability, weak institutional readiness, partial service integration, and limited trust in data governance. The novelty of this study lies in identifying a local digital readiness gap, where national digital identity policy is formally available but cannot produce inclusive public value without village-level facilitation. Theoretically, the study extends digital governance literature by explaining grassroots digital identity effectiveness as a socio-institutional process shaped by policy translation, bureaucratic capacity, citizen capability, trust, and co-production, rather than by application availability alone. The study recommends community-based digital mentoring, stronger coordination between Dukcapil and village officials, and service indicators that measure accessibility, efficiency, trust, and citizen participation.